2002
DOI: 10.1016/s0002-9440(10)64378-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Chemokine Receptors CCR4, CCR5, and CXCR3 by Human Tissue-Infiltrating Lymphocytes

Abstract: Differential expression of adhesion molecules and chemokine receptors has been useful for identification of peripheral blood memory lymphocyte subsets with distinct tissue and microenvironmental tropisms. Expression of CCR4 by circulating memory CD4 ؉ lymphocytes is associated with cutaneous and other systemic populations while expression of CCR9 is associated with a small intestine-homing subset. CCR5 and CXCR3 are also expressed by discrete memory CD4؉ populations in blood, as well as by tissueinfiltrating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
179
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(198 citation statements)
references
References 37 publications
18
179
1
Order By: Relevance
“…Previous studies have shown that CXCR3 is expressed, together with several other CKR, on T cells in inflamed tissues [1][2][3][4][5][6], and in dermal inflammation the T cell expression of the skin-homing CKR CCR4 and CCR10 has been the subject of focus [12][13][14][15][16]. In addition, CCR2, CCR5 and CXCR6 are also present on infiltrated T cells [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that CXCR3 is expressed, together with several other CKR, on T cells in inflamed tissues [1][2][3][4][5][6], and in dermal inflammation the T cell expression of the skin-homing CKR CCR4 and CCR10 has been the subject of focus [12][13][14][15][16]. In addition, CCR2, CCR5 and CXCR6 are also present on infiltrated T cells [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although the CXCR3 + subset is a minority (*15%) of T cells within the memory T cell subpopulation, it includes most of the T cells recruited to dermal inflammation. This may be because of the importance of CXCR3 in this migration, or because CXCR3 + T cells co- express other CKR, such as CCR2, CCR4 and CCR5, which contribute to T cell infiltration [13]. Indeed, rat memory CD4 T cells are *15% CCR2 + , 10-15% CCR4 + , *2% CXCR6 + and have low levels of CCR5 message, while CD8 T cells are *9% CCR2 + and *3% CXCR6 + , and have low levels of CCR4 and CCR5 (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also detected on T cells in psoriatic lesions and induced blisters (10,11). The production of CCR4 ligands in atopic dermatitis lesions (7) is thought to attract CCR4 + CD4 T cells (12), but the relationship between CCR4 and the migration of multiple CCR4 + T cell subsets is unknown.…”
mentioning
confidence: 99%
“…Other CKRs also contribute to skin homing of T cells. Ligands of CXCR3 and CCR10 are produced in inflamed skin, and both CXCR3 and CCR10 are expressed on skin-infiltrating T cells in humans (11,13). Blockade of CXCR3 was shown to inhibit 90% of the migration of T cell lymphoblasts to dermal inflammation (14), even though CCR4 is coexpressed on about half of the CXCR3 + CD4 T cells (6).…”
mentioning
confidence: 99%